PENGEMBANGAN ALAT PERMAINAN EDUKATIF “KARTU BACA NGAJI ASYIK” UNTUK ANAK USIA DINI - Septiani Selly Susanti (LPPM STAI DARUSSALAM LAMPUNG, 2020)
This research is useful for parents, teachers, and lecturers in an effort to create a tool that is able to condition learning to be fun and enjoyable for children. Childhood is a time when they prefer to play and move. Making children comfortable in the early childhood learning process is the main key. This is because the world of children is a world of joy, warmth, and joy, so that all activities intended for children must always give birth to comfort. Here, educational play tools become one of the media that can make children's learning fun and enjoyable. When children learn with pleasure, their brains will easily receive knowledge and life experiences well and quickly. The learning process for children becomes easy. In the book